2014
DOI: 10.1371/journal.pone.0099852
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of DNA Metabarcoding to Fungal Conservation: Diversity Assessment, Habitat Partitioning and Mapping Red-Listed Fungi in Protected Coastal Salix repens Communities in the Netherlands

Abstract: Western European coastal sand dunes are highly important for nature conservation. Communities of the creeping willow (Salix repens) represent one of the most characteristic and diverse vegetation types in the dunes. We report here the results of the first kingdom-wide fungal diversity assessment in S. repens coastal dune vegetation. We carried out massively parallel pyrosequencing of ITS rDNA from soil samples taken at ten sites in an extended area of joined nature reserves located along the North Sea coast of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 64 publications
5
37
0
1
Order By: Relevance
“…Detection of five phylogenetically diverse fungal phyla from asymptomatic plant rhizosphere and tissues demonstrates that S. chamaejasme harbors a diverse group of rhizospheric and endophytic mycobiota. The very low proportion of Chytridiomycota and Glomeromycota taxa found in the present study is similar with other studies (Geml et al 2014;Mouhamadou et al 2011). These results are similar with other cultureindependent molecular studies dealing with the rhizospheric fungal communities of different plant (Geml et al 2014), and also in agreement with previous reports on endophytic fungal communities of grassy tissues or leaves, stems and roots of different medicinal plant hosts (Kusari et al 2013;Sánchez Márquez et al 2010), which have found coincidental distribution patterns of ascomycetous fungi.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Detection of five phylogenetically diverse fungal phyla from asymptomatic plant rhizosphere and tissues demonstrates that S. chamaejasme harbors a diverse group of rhizospheric and endophytic mycobiota. The very low proportion of Chytridiomycota and Glomeromycota taxa found in the present study is similar with other studies (Geml et al 2014;Mouhamadou et al 2011). These results are similar with other cultureindependent molecular studies dealing with the rhizospheric fungal communities of different plant (Geml et al 2014), and also in agreement with previous reports on endophytic fungal communities of grassy tissues or leaves, stems and roots of different medicinal plant hosts (Kusari et al 2013;Sánchez Márquez et al 2010), which have found coincidental distribution patterns of ascomycetous fungi.…”
Section: Discussionsupporting
confidence: 94%
“…It is reasonable that soil borne fungi are more prevalent and diversified than air borne fungi (The fungi that infect aerial plant tissues via air-borne spores) (Ghimire et al 2011). These results are similar with other cultureindependent molecular studies dealing with the rhizospheric fungal communities of different plant (Geml et al 2014), and also in agreement with previous reports on endophytic fungal communities of grassy tissues or leaves, stems and roots of different medicinal plant hosts (Kusari et al 2013;Sánchez Márquez et al 2010), which have found coincidental distribution patterns of ascomycetous fungi. Similar result was found by Ghimire et al (2011), who obtained fungal isolates from root tissues was almost three times higher than that from shoot tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(2011) as reference. We used a 97% sequence similarity clustering threshold as has been routinely done in fungal ecology studies (e.g., O'Brien et al ., 2005; Higgins et al ., 2007; Geml et al ., 2008, 2009; Amend et al ., 2010; Tedersoo et al ., 2010; Geml et al ., 2012; Kauserud et al ., 2012; Brown et al ., 2013; Blaalid et al ., 2013; Geml et al ., 2014a). Global singletons were discarded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular techniques will assist greatly in tackling currently intractable aspects. A genealogical concordance approach to the rigorous recognition of phylogenetic species is increasingly applied to fungi, and barcoding is a practical tool for identification (Geml et al 2014). Metabarcoding provides unprecedented characterization of the fungal community in any substrate (e.g., soil, insect guts, plant roots or leaves).…”
Section: Characteristic Issuementioning
confidence: 99%